2015
DOI: 10.5433/1679-0359.2015v36n6supl2p4323
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium spp. in wild animals living in the Cascavel city park, Paraná, Brazil

Abstract: Digestive and respiratory tracts parasite's protozoan, Cryptosporidium spp. now-a-days is a major zoonotic agent, it causes self-limiting diarrhea, remaining in the body passively until the moment immune system decreases, leading to an increase in its multiplication in the mucosa and appearance of clinical signs. As there are few studies on cryptosporidiosis in wild free-living and captive animals, especially in Brazil, this study aimed to identify the presence of Cryptosporidium spp. in feces of captive anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In Brazil, studies on cryptosporidiosis in ruminants have primarily been performed in the Southeast, mainly in the states of Rio de Janeiro (COSENDEY et al, 2008;FIUZA et al, 2011), Minas Gerais (GARCIA & LIMA, 1993;GARCIA & LIMA, 1994;LIMA et al, 2013), andSão Paulo (AQUINO et al, 2015;COELHO et al, 2016;FEITOSA et al, 2004;FÉRES et al, 2009;PAZ E SILVA et al, 2013SEVÁ et al, 2010;SILVA-JUNIOR et al, 2011). In the state of Paraná, infection with Cryptosporidium was evaluated in captive birds (NAKAMURA et al, 2009), dogs with diarrhea (NAVARRO et al, 1997), horses (FUJII et al, 2014, wild birds and mammals (SNAK et al, 2015), cattle (TOLEDO et al, 2017 and sheep (SNAK et al, 2017). However, epidemiological studies have not been conducted on cryptosporidiosis in ruminants of the north pioneer mesoregion of Paraná.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies on cryptosporidiosis in ruminants have primarily been performed in the Southeast, mainly in the states of Rio de Janeiro (COSENDEY et al, 2008;FIUZA et al, 2011), Minas Gerais (GARCIA & LIMA, 1993;GARCIA & LIMA, 1994;LIMA et al, 2013), andSão Paulo (AQUINO et al, 2015;COELHO et al, 2016;FEITOSA et al, 2004;FÉRES et al, 2009;PAZ E SILVA et al, 2013SEVÁ et al, 2010;SILVA-JUNIOR et al, 2011). In the state of Paraná, infection with Cryptosporidium was evaluated in captive birds (NAKAMURA et al, 2009), dogs with diarrhea (NAVARRO et al, 1997), horses (FUJII et al, 2014, wild birds and mammals (SNAK et al, 2015), cattle (TOLEDO et al, 2017 and sheep (SNAK et al, 2017). However, epidemiological studies have not been conducted on cryptosporidiosis in ruminants of the north pioneer mesoregion of Paraná.…”
Section: Introductionmentioning
confidence: 99%
“…The lower prevalence may be linked to the remote location of the Zoo in a mountain forest that limited the exposure of animals to foreign pathogens from domestic animal reservoirs. Another study on wild animals living in the Cascavel city park in Paraná, Southern Brazil, reported a relatively higher overall prevalence of 49.15% for Cryptosporidium specie (Snak et al, 2015). The high infection rate was attributed to the herbivorous feeding behaviour of most of the animals studied, which facilitates the ingestion of oocysts in the soil and vegetation.…”
Section: Discussionmentioning
confidence: 90%